Progress in understanding the role and mechanism of miRNAs in osteoporosis - Feifei Meng; Feifei Meng; Changwei Yang; Na Li; Huaxin Wang (Frontiers in Endocrinology)
Please confirm that the below Frontiers AI generated Alt-Text is an accurate visual description of your Figure(s). These Figure Alt-text proposals won't replace your figure captions and will not be visible on your article. If you wish to make any changes, kindly provide the exact revised Alt-Text you would like to use, ensuring that the word-count remains at approximately 100 words for best accessibility results. Further information on Alt-Text can be found here.Osteoporosis is a systemic metabolic disorder characterized by compromised bone strength and increased fracture risk. Exosomes, extracellular vesicles measuring 40–160 nm in diameter, are critical mediators of intercellular communication. Among their bioactive components, microRNAs (miRNAs) have garnered attention for their role in the pathogenesis of Osteoporosis. Through complementary binding to the 3′ untranslated regions of target genes, miRNAs regulate key processes such as bone formation, bone resorption, angiogenesis, and bone immunity. This review provides a comprehensive summary of the regulatory roles and underlying mechanisms of miRNAs in osteoporosis, offering insights into potential therapeutic strategies.